ANALISIS KEPUASAN KERJA KARYAWAN PADA HOTEL SRI INDRAYANI PEKANBARU - Ori Tri Wulandari; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this research is to know how the satisfaction of employee’s work in Sri Indrayani and how to improve the satisfaction of employee’s work in Sri Indrayani Hotel.This research is used descriptive quantitative methods. There were 30 sample all employee. The data collection techniques in this research used observation, interview, and quesionnaires. The likert scale was used to measure the intervals in quantitative data.This research theory used Harold E. Burt in the book of Pandji Anoraga (2005:82) theory. This theory divides job satisfaction into 3 categories: factor relationship between employees, individual factors, external factors.The analysis result of the employee’s work satisfaction is quite good in Sri Indrayani Hotel Pekanbaru. It is proved that the managemen of Sri Indrayani Hotel Pekanbaru have improved their employee’s work satisfaction maximally. As know in improving the employee’s work of satisfaction in Sri Indrayani Hotel Pekanbaru with challenged work mentally, good appreciation, good condition of work and supportive relationship.Keywords: promotion and promotion mix.